2022
DOI: 10.1007/s10460-022-10311-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome-edited versus genetically-modified tomatoes: an experiment on people’s perceptions and acceptance of food biotechnology in the UK and Switzerland

Abstract: Biotechnology might contribute to solving food safety and security challenges. However, gene technology has been under public scrutiny, linked to the framing of the media and public discourse. The study aims to investigate people’s perceptions and acceptance of food biotechnology with focus on transgenic genetic modification versus genome editing. An online experiment was conducted with participants from the United Kingdom (n = 490) and Switzerland (n = 505). The participants were presented with the topic of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…This can lead to building trust amongst consumers. Findings show that, for example, consumers accept new technologies more if they are aware of the benefits it may bring, even if there are some perceived risks (Hartmann et al, 2018;Bearth et al, 2022;Busch et al, 2020).…”
Section: When the Topic Is Complex And Evidence Is Not Conclusive Com...mentioning
confidence: 99%
See 3 more Smart Citations
“…This can lead to building trust amongst consumers. Findings show that, for example, consumers accept new technologies more if they are aware of the benefits it may bring, even if there are some perceived risks (Hartmann et al, 2018;Bearth et al, 2022;Busch et al, 2020).…”
Section: When the Topic Is Complex And Evidence Is Not Conclusive Com...mentioning
confidence: 99%
“…Furthermore, in the context of biotechnology in the UK and Switzerland, Bearth et al (2022) found that the form of media consumers received information from on the risks and benefits of production techniques did not have a significant impact on their willingness to accept the technique. Therefore, consumers receiving information from journalistic media were no more trusting than when they received information from social media or blogs.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Our analysis use farmed genome-edited salmon in Norwegian ocean facilities as a case with the purpose of elaborating a sustainability assessment framework for genome-edited salmon in aquaculture using three sources of information; strategy and policy documents published by governmental offices and industry organizations; relevant GMO regulations and operationalization reports; and qualitative empirical data from 19 semi-structured interviews with Norwegian key stakeholders, and four semi-structured citizen groups. This work contributes to the growing knowledge on stakeholder and citizens views on genome-editing in food production (Bearth et al, 2022;Busch et al, 2022;Kantar., 2020;van der Berg et al, 2021), and to the more general discussion of how to operationalise sustainability in aquaculture.…”
Section: Introductionmentioning
confidence: 95%